Incidence, prevalence and associated factors of mother-to-child transmission of HIV, among children exposed to maternal HIV, in Belgaum district, Karnataka, India - Potty, Rajaram Subramanian (BMC Public Health, 2019)
BACKGROUND: India lacks data on the incidence of Paediatric HIV. In 2010, the Indian Council of Medical Research commissioned a task force study to estimate the paediatric HIV burden in Belgaum district, Karnataka, India. We estimated the HIV incidence, prevalence and associated risk factors of mother to child transmission of HIV among children exposed to maternal HIV by age 24 months. METHODS: We included Belgaum resident pregnant women who tested HIV positive between January 1st, 2011 and May 31st, 2013 and who provided consent. Their babies were tested for HIV at three time intervals using DNA PCR dry blood spot (DBS) method at 6–10 weeks and 6–9 months, and using Antibody tests at 18–24 months of age. We estimated cumulative incidence using survival analysis that considered censoring of cases and prevalence rates of HIV by age 24 months. Using competing-risk survival regression model, we examined the correlates of transmission of HIV among babies exposed to maternal HIV. RESULTS: Among 487 children of HIV positive mothers recruited in the study, the cumulative incidence rate by 24 months of age was 4.8 per 1000 person months [95% CI: 3.5–6.6]. The HIV prevalence rate among babies exposed to maternal HIV until 24 months was 7.8% [95% CI: 5.7–10.7]. Mother’s age above 30 years, and breastfeeding duration of more than six months were factors that significantly increased the HIV transmission; adjusted hazard ratio (AHR) 6.98 [95% CI: 1.73–28.16] and 5.28 [95% CI, 1.75–15.90], respectively. The risk of MTCT was significantly reduced if both mother and baby had received Nevirapine at delivery [AHR 0.25; 95%CI: 0.10–0.61] and if either mother or baby had been given Nevirapine at delivery [AHR 0.12; 95%CI: 0.03–0.49]. CONCLUSION: The study findings suggest that mother’s age above 30 years and breastfeeding beyond 26 weeks is associated with higher rates of HIV transmission from mother to child. It confirms the benefits of providing anti-retrovirals (Nevirapine) in reducing mother to child transmission of HIV. Effective strategies to promote safe infant feeding practices, including avoidance of mixed feeding beyond 26 weeks among HIV infected mothers, is critical to reduce incidence of paediatric HIV in India.